PARTICIPAÇÃO DA POPULAÇÃO INDÍGENA SUL-MATO-GROSSENSE NOS DIREITOS POLÍTICOS PASSIVOS - Almeida Pereira, Guilherme; Knapp, Cássio (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2025)
ABSTRACT: In Brazil, there is an increase in the number of people who declare themselves indigenous, with Mato Grosso do Sul being the third state with the largest share of this population. In this context, this article aims to identify the reality of the participation of the indigenous population of Mato Grosso do Sul in the exercise of passive political rights, consistent with the citizen’s ability to be elected and exercise an elective mandate. Using bibliography, data from IBGE, the Superior Court and collected in interviews and questionnaires, it examines the concept of indigenous people; provides a national and local overview of this population; discusses the concept and types of political rights; addresses the phenomenon of political representation; and analyzes the reality and vision of elected indigenous people on the subject. With the research it was possible to observe that there is no effective indigenous participation in passive political rights, motivated mainly by economic and cultural issues and lack of identity of political parties in defense of the indigenous cause. Keywords: Passive political rights, indigenous participation, reality in Mato Grosso do Sul.